Deep Learning untuk Mendukung Pemahaman Mendalam dalam Pembelajaran Matematika: Pengabdian - Sity Rahmy Maulidya; Sri Ulfa Insani; Zulfah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This Community Service project aimed to introduce and enhance understanding of deep learning in mathematics education among elementary school teachers. The program also facilitated the use of Quizizz platform ti help teachers create interactive and engaging assessment experiences. Considering that elementary education serves as the foundational stage for students' future mathematical competence, this initiative seeks to empower teachers to establish meaningful and effective learning experiences. The program not only promotes deeper conceptual understanding among students but also encourages the development of essential 21st-century skills, often referred to as the 4Cs: critical thinking, creativity, communication, and collaboration. Attended by 30 teachers, the program combined conceptual learning with practical implementation. Results showed a significant improvement in participants’ understanding of deep learning and their ability to use Quizizz effectively. The initiative also fostered teacher enthusiasm and commitment to applying these approaches in the classroom. This program is expected to contribute positively to the development of meaningful learning environments and the cultivation of students’ 21st-century skills, including critical thinking, creativity, communication, and collaboration.